THE IMPACT OF THE REFORMS OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS ON STRENGTHENING THE EFFECTIVENESS OF THE EUROPEAN COURT OF HUMAN RIGHTS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The European Court of Human Rights (ECtHR) is the most famous andperhaps the most successful institution of the Council of Europe (CoE).Within the CoE, there is an informal opinion that the Court is a "victim"of its own success. The ECtHR has been continuously facing anincreasing influx of applications by European citizens pointing to humanrights violations. This phenomenon has necessitated the implementationof effective reforms, both in the European Convention on Human Rights(ECHR) and in the modalities of functioning of the ECtHR. This paperanalyzes the effects of reforms that have been implemented over theyears, with regard to the basic text of the ECHR, with a focus on theefficiency of the functioning of the Court as well as the overall systemrelated to the protection of human rights. To that end, a special review ismade of the content of the declarations arising from high levelconferences organized by certain Member States during theirchairmanship of the Committee of Ministers. In this context, this paperanalyzes the declarations that arise as a result of high-level conferencesin Interlaken, Izmir, Brighton, Brussels and Copenhagen.